Aggregate measures of ecosystem services: can we take the pulse of nature?. Issue 1 (1st February 2005) - Meyerson, Laura A.; Baron, Jill; Melillo, Jerry M.; Naiman, Robert J.; O'Malley, Robin I.; Orians, Gordon; Palmer, Margaret A.; Pfaff, Alexander SP; Running, Steven W.; Sala, Osvaldo E.
Abstract : National scale aggregate indicators of ecosystem services are useful for stimulating and supporting a broad public discussion about trends in the provision of these services. There are important considerations involved in producing an aggregate indicator, including whether the scientific and technological capacity exists, how to address varying perceptions of the societal importance of different services, and how to communicate information about these services to both decision makers and the general public. Although the challenges are formidable, they are not insurmountable. Quantification of ecosystem services and dissemination of information to decision makers and the public is critical for the responsible and sustainable management of natural resources.